Audit Quality of Financial Statements of Commercial Banks, Whether or not There is a Difference in Audit Quality Provided by Big4 and Non-Big4 Audit Firms - Pham, Huy Hung; Nguyen, Thi Hong Lam; Doan, Van Anh; Tran, Manh Tuong (International Journal of Economics and Financial Issues, 2024)
This study is conducted for the purpose of investigating the influence of factors on the audit quality of financial statements of Vietnamese commercial banks. Also consider whether or not there is a difference in the quality of audits provided by Big4 and Non-Big4 auditing firms from the perspective of independent auditors. Data was collected from 226 respondents working in 20 independent auditing firms in Vietnam (4 Big4 auditing firms and 16 Non-Big4 auditing firms), holding positions such as audit firm managers, audit team leaders and auditors, who are directly involved in the audit. Sampling was conducted selectively from April 2023 to August 2023. By quantitative research method, with the support of SPSS22 software. The research results show that the factors that have an important influence on the audit quality of financial statements of Vietnamese commercial banks in descending order include: in-depth capacity of auditors; characteristics of commercial banks; time pressure; audit methods; quality control of auditing enterprises and legal systems; auditor independence; standard compliance; working conditions of auditing enterprises; size and reputation of auditing enterprises. However, the results of the study found no difference in the audit quality of financial statements of Vietnamese commercial banks between auditors of Big-4 and Non-Big-4 auditing enterprises. Based on the research results, a number of recommendations are made to auditors and auditing companies to improve the quality of auditing financial statements of commercial banks in the coming time.